Effect of Neem Oil Supplementation on Growth Performance and Hematobiochemical Profile in Broilers - Patil, R. M.; Ingole, R. S.; Pathak , V. P.; Joshi , M. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A study was undertaken on one hundred day old broiler chicks to obtain information about safe  levels of neem oil supplementation in broiler feed for economic poultry farming. Significant decrease  in body weight and feed consumption was observed in birds on addition of 0.4 per cent neem oil.  Hematological study revealed non significant difference between treatment group and control group  birds. Birds given 0.4 % neem oil showed numerical increased TLC, absolute heterophil and absolute  lymphocyte count when compared with control and other treatment group birds (0.1, 0.2 and 0.3  % neem oil). Average plasma glucose level showed dose dependent hypoglycemic response. Serum  total protein and serum globulin level showed significant decrease at 0.4 per cent level suggesting  adverse effect in broilers. It is thus concluded that neem oil supplementation up to 0.3 per cent  in feed could be used safely in broilers.